Let's eat food - Capital Cities Television Productions (Del Mar, Calif. : CRM/McGraw-Hill Films, 1976)
Examines the relationship between health and diet. Considers specific topics such as coronary heart disease, nutritional deprivation, iron deficiencies, and the relationship of sugar to health
Keywords: Nutritionally induced diseases; Nutrition